PENGARUH INITIAL MOISTURE CONTENT DAN MASSA TEPUNG PADA PROSES PENGERINGAN TEPUNG TAPIOKA MENGGUNAKAN PENGERING UNGGUN FLUIDISASI - Ika Permatasari; Laela Khaerunnisa Eugenia; S Suherman (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
In tapioca starch home industry, flour drying still using conventional drying which relies on sunlight that cause product quality not uniform and under standard. From conventional drying weakness, fluidized bed drying technology can be applied to flour drying. The purpose of this research is to make drying curve, studied the effect of feed mass and initial moisture content to drying, and quality test of tapioca starch product. In this study, dependent variables are operating temperature 60 °C, drying air flow rate 2,7 m/s, operation time 45 minutes, and humidity inlet air. The independent variables are initial moisture content and feed mass.The result obtained is the value of RH and T air dryer air dryer exit out obtained through the curve will show the rate of drying. Analysis of products made with white test, starch content, moisture content, and fiber content. During drying process, relative humidity and humidity of outlet drying air are decreases, while temperature outlet drying air is increase. The effect of mass feed to moisture content product profile is the less of mass feed to be dried, and flour can dry faster. The effect of mass feed to drying rate is the less mass feed to be dried, the higher drying rate.